The Ukrainian Education Development of XIX Century through a Prism of the Ideas of M.Drahomanov - Vitaliy Mats’ko (Pedagogical Discourse, 2013)
The conceptual foundations of education in Ukraine in the second half of the nineteenth century are modeled on the background of specific historical and pedagogical examples and famous works of a Ukrainian scientist M.Dragomanov. It is proved that the educational environment was not favorable for the development of national culture, language as it was carefully controlled by  royal circulars,  decrees, what led to harassment and restrictions of the national school. The ban was based on the historical statement of denying a Ukrainian language as such, and that a Ukrainian movement in education and culture is nothing like polish intrigue. The gaduate of Kiev University Michail Dragomanov opposed his active practice against the Tsarist officials ignorance, national and social oppression. Scientific works of Drahomanov were as a matrix of education, an inexhaustible model source and kind of  behaviour, patriotism and moral strength of teacher, scholar, historian, folklorist, journalist, writer, and philosopher.